Anaemia in acute coronary syndrome patients: a study from rural tertiary care centre of India - Verma, Vivek Kumar; Singh, Durga Prasad; Kela, Dheeraj; Vijayavarman, V.; Singh, Geeta (International Journal of Research in Medical Sciences, 2018)
Background: Acute coronary syndromes (ACS) are an imbalance between myocardial oxygen supply and demand, and the presence of anaemia further potentiates this imbalance. The burden of anaemia in patients presenting with acute coronary syndromes (ACS) is significant. Anaemia has the potential to worsen myocardial ischemic insult by decreasing the oxygen content of the blood supplied to the jeopardized myocardium. Methods: A total of 148 patients with ACS were recruited in the study from October 2016 to December 2017 in Medicine and Cardiology Department of UPUMS Saifai, India. All patients were subjected to a detailed history and thorough clinical examination and investigations after obtaining informed consent. Patient having any other diseases known to cause anaemia were excluded. Results: Mean age of patients was 58.5 years. 72.97% were vegetarian and 27.03% were non-vegetarian. Most common morphological type of anaemia was dimorphic anaemia followed by macrocytic and microcytic hypochromic respectively. Iron deficiency anaemia was most common type of anaemia followed by vitamin B12 deficiency and mixed (Iron and vitamin B12 deficiency). 45.28% anaemic patients had no symptoms of blood loss. Most common symptom of blood loss was bleeding per rectum followed by malena. Severity of acute coronary syndrome was more in subjects having anaemia which was evident by higher incidence of anaemia in subjects having ST elevation myocardial infarction (STEMI). The incidence of anaemia was low in case of Non ST elevation Myocardial Infarction (NSTEMI) and Unstable angina (UA). The results of the present study have been compared to those from India. Conclusions: Higher incidence of anaemia was reported in subjects having acute coronary syndrome. Incidence of anaemia in STEMI patients was greater than NSTEMI and unstable angina patients. Severe form of acute coronary syndrome i.e. STEMI was associated with higher incidence of anaemia.